PhaC Synthases and PHA Depolymerases: The Enzymes that Produce and Degrade Plastic - Amara, Amro A.; Moawad, and Hassan (IIUM Engineering Journal, 2011)
PHAs are a group of intracellular biodegradable polymer produced by (most) bacteria under unbalanced growth conditions. A series of enzymes are involved in different PHAs synthesis, however PhaC synthases are responsible for the polymerization step. PHAs are accumulated in bacterial cells from soluble to insoluble form as storage materials inside the inclusion bodies during unbalanced nutrition or to save organisms from reduces equivalents. PHAs are converted again to soluble components by another pathways and enzymes for the degradation process. PHAs depolymerases are the responsible enzymes. This review is designed to give the non-specialists a condense background about PHAs especially for researcher and students in medicinal and pharmaceutical filled. ABSTRAK: PHAs (polyhydroxyalkanoate) merupakan sekumpulan polimer terbiodegradasikan intrasel yang dihasilkan oleh (kebanyakan) bakteria di bawah keadaan tumbesaran tak seimbang. Satu rangkaian enzim terlibat dalam sistesis PHAs yang berbeza, namun sintesis PhaC bertanggungjawab dalam peringkat pempolimeran. PHAs dikumpulkan dalam sel bakteria dari bentuk larut dan tak larut sebagai bahan simpan di dalam jasad terangkum semasa nutrisi tak seimbang atau untuk menyelamatkan organisma daripada pengurangan tak keseimbangan. PHAs ditukarkan sekali lagi kepada komponen larut dengan cara lain dan enzim lain untuk proses degradasi. PHAs depoly-merases (enzim yang memangkin penguraian makro molekul kepada molekul yang lebih mudah) merupakan enzim yang bertanggunjawab. Kajian semula ini direka untuk memberi mereka yang bukan pakar, satu ringkasan tentang PHAs terutamanya penyelidik dan penuntut dalam bidang peubatan dan farmaseutikal.